Development of Helicobacter pylori BabA minimal binding domain as a novel biomimetic moiety for gastric-targeted drug delivery - Mohammed, Aymen (2020)
The need for efficient drug delivery systems / better treatment for human disorders remains a challenge in medicine. This demand could be addressed by developing a new strategy that assist the formulation to act specifically. Some drugs would benefit from targeting the gastric epithelium and retain the therapeutic in the stomach. However, drugs absorbed through the stomach or upper small intestine have a narrow absorption window. Developing a drug delivery system that can adhere to the surface of the gastric epithelial cells will significantly increase drug transit time and overcome this limitation.